Augmented Reality Development Opportunities in Geometry Learning for Elementary Students - Elika Yuana Fitrianingsih; Muhammad Akhyar; Agus Efendi (Universitas Pendidikan Ganesha, 2023)
Educational institutions will basically get many benefits from using technology, such as augmented reality technology which is designed to support the learning process in the classroom, plus augmented reality technology can be operated on smartphones. This study aims to analyze the opportunities for the use of smartphones in the context of innovation in the development of learning media with augmented reality formats. A qualitative approach was used in this study with a survey method. The population used is Madrasah Ibtidaiyah students with a sample was 127 students. The data collection technique in this study was a non-test technique, with the data collection instrument being a questionnaire. The results of this study indicate that smartphones are a technology that is quite familiar to students, considering that most students have them, students also like learning activities that utilize smartphones because they contain several components such as text, graphics, narration, video and even animation. The results of this study can certainly be the basis for developing an augmented reality-based learning media product considering the components that make students motivated to learn are contained in it. Through this research, it is hoped that new learning resource innovations will emerge with the hope that students can be facilitated in learning the material and mastering the various competencies they need.